Mycosis Fungoides of the Oral Cavity: Fungating Tumor Successfully Treated with Electron Beam Radiation and Maintenance Bexarotene. (15th December 2016) - Bassuner, Juri; Miranda, Roberto N.; Emge, Drew A.; DiCicco, Beau A.; Lewis, Daniel J.; Duvic, Madeleine
Abstract : Oral involvement in mycosis fungoides is unusual and portends a poor prognosis. The clinical findings of three new cases are described along with a differential diagnosis and review of the literature. For brevity, only one patient is discussed in detail below whereas the other two cases are solely described in table form. The patient had a four-year history of mycosis fungoides before developing an exophytic tongue tumor. He was treated with local electron beam radiation and is disease-free to date while being on maintenance therapy with oral bexarotene. Analysis of the data collected from our review of the literature and the present cases reveal key insights.